Resistance to Recombinant Human Erythropoietin Therapy in a Rat Model of Chronic Kidney Disease Associated Anemia - Garrido, Patrícia (2016)
This study aimed to elucidate the mechanisms explaining the persistence of anemia and resistance to recombinant human erythropoietin (rHuEPO) therapy in a rat model of chronic kidney disease (CKD)-associated anemia with formation of anti-rHuEPO antibodies. The remnant kidney rat model of CKD induced by 5/6 nephrectomy was used to test a long-term (nine weeks) high dose of rHuEPO (200 UI/kg bw/week) treatment. Hematological and biochemical parameters were evaluated as well as serum and tissue (kidney, liver and/or duodenum) protein and/or gene expression of mediators of erythropoiesis, iron metabolism and tissue hypoxia, inflammation, and fibrosis. Long-term treatment with a high rHuEPO dose is associated with development of resistance to therapy as a result of antibodies formation. In this condition, serum EPO levels are not deficient and iron availability is recovered by increased duodenal absorption. However, erythropoiesis is not stimulated, and the resistance to endogenous EPO effect and to rHuEPO therapy results from the development of a hypoxic, inflammatory and fibrotic milieu in the kidney tissue. This study provides new insights that could be important to ameliorate the current therapeutic strategies used to treat patients with CKD-associated anemia, in particular those that become resistant to rHuEPO therapy.